If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(y + -2) + 8y = 0 Reorder the terms: 5(-2 + y) + 8y = 0 (-2 * 5 + y * 5) + 8y = 0 (-10 + 5y) + 8y = 0 Combine like terms: 5y + 8y = 13y -10 + 13y = 0 Solving -10 + 13y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 13y = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 13y = 0 + 10 13y = 0 + 10 Combine like terms: 0 + 10 = 10 13y = 10 Divide each side by '13'. y = 0.7692307692 Simplifying y = 0.7692307692
| 100c=1+5c | | (6w^2+5w-7)(3w-4)= | | =x+0.07 | | 7x+7=-4+5x+15 | | 4x-4-5x=-2 | | F(x)=6-4x | | 12(x+3)=4(2x+9)4x | | 122=x-8(1-8x) | | 5(-2x+9)=45 | | x-48+x=180 | | 5i=60 | | X^2-12-45=0 | | 5x-1-4=x+7 | | 3m+12-4m=-7m+14 | | 6-4n=-5n+2 | | 235=-5(6v-5) | | m^2-4=60 | | 180+24b=27b | | 12-3(4x+3)=-2x+23 | | 4r-8=8x+6 | | 2(-2k+3)=28+7k | | 13.0x-50=180 | | 80=2l+2(14) | | f=why | | 10x-5y=6.6 | | 12k=-60 | | 15x^2-3x-54=0 | | 12x^3+4x^2-5x=0 | | 16x^2=24x | | 11x-20+2x=5(x+40) | | (4n+8)=6 | | 6y+8=7x-12 |